Immunogenicity, safety and reactogenicity of Ad26.RSV.preF/RSV preF protein vaccine in adults aged 60 to 75 years: A comparison of phase 2b and phase 3 clinical trial material - Archana Jastorff; Arangassery Rosemary Bastian; Nynke Ligtenberg; Vladislav Klyashtornyy; Benoît Callendret; Esther Heijnen (Human Vaccines & Immunotherapeutics)
The Ad26.RSV.preF/RSV preF protein vaccine has previously demonstrated efficacyin protecting older adults against respiratory syncytial virus (RSV)–related lower respiratory tract disease in a phase 2b study. This study compared the immunogenicity of vaccine clinical trial material (CTM) representative of phase 2b clinical studies with CTM used in phase 3 clinical studies. A total of 248 adults aged 60–75 years, randomized in a 1:1 ratio, received one dose of either phase 3 CTM or phase 2b CTM. Solicited adverse events (AEs), unsolicited AEs, and serious AEs (SAEs) were assessed for 7-d, 28-d, and 6-month periods post-vaccination, respectively. RSV preF-ELISA antibody titers and RSV neutralizing titers were measured before and 14 d after vaccination. The phase 3 CTM-induced preF-ELISA response at Day 15, in terms of geometric mean titer, was shown to be non-inferior to that induced by phase 2b CTM. The RSV neutralizing antibody titers were also similar in the two groups at Day 15. The safety profile in terms of solicited AEs, unsolicited AEs, or SAEs was in general similar between the phase 3 CTM and phase 2b CTM groups, and solicited AEs were mostly mild to moderate in intensity. No related SAEs were reported, and no safety concerns were identified.